Incidence of Maxillofacial Trauma at Royal Prima Hospital - Fauziah, Dinda; Febrini, Dewi; Alexander, Rico (Newinera Publisher, 2025)
A study investigated the prevalence rates together with the sociodemographic features and the types of maxillofacial fractures and their causes for patients seeking treatment at Royal Prima Hospital in Medan during 2021–2023. This research employed a cross-sectional descriptive observational design using data retrieved from past records which documented 26 maxillofacial trauma patients. Selection of proper cases followed a purposive sampling method. The researchers used descriptive statistics in combination with cross-tabulations to evaluate associations among variables including gender distribution and patient age as well as fracture type and trauma etiology. The population of male patients exceeded females (69.2%) at a rate of 42.3% within the 11–20-year age category. Traffical accidents represented the primary reason behind traumatic injuries (61.5%) which mostly happened during motorcycle accidents. Lesions of the Le Fort I region of the maxilla occurred in 38.5 percent of cases and became the most prevalent fracture type. Hospital admission occurred for 65.4% of patients while surgical treatment became necessary for almost half of the total patients. The management of trauma patients became more complicated because 38.5% of patients presented systemic injuries with their facial trauma. Traffic accidents caused most of the maxillofacial trauma cases which mainly affected young male individuals at Royal Prima Hospital. The most common confrontational facial fracture presented as Le Fort I types among patients. The results demonstrate an immediate demand to create specific public health programs together with intensified traffic regulations and improved trauma medical systems in order to decrease facial injuries and achieve better patient recovery.